TGR5 signaling reduces neuroinflammation during hepatic encephalopathy. (10th September 2015) - McMillin, Matthew; Frampton, Gabriel; Tobin, Richard; Dusio, Giuseppina; Smith, Jenny; Shin, Hope; Newell‐Rogers, Karen; Grant, Stephanie; DeMorrow, Sharon
Abstract Hepatic encephalopathy (HE) is a serious neurological complication of acute and chronic liver failure. Expression of the neurosteroid/bile acid receptor Takeda G protein‐coupled receptor 5 (TGR5) has been demonstrated in the brain and is thought to be neuroprotective. However, it is unknown how TGR5 signaling can influence the progression and associated neuroinflammation of HE. HE was induced in C57Bl/6 mice via intraperitoneal injection of azoxymethane (AOM) and tissue was collected throughout disease progression. TGR5 expression was elevated in the frontal cortex following AOM injection in mice. The cellular localization of TGR5 was found in both neurons and microglia in the cortex of C57Bl/6 mice. Central infusion of the TGR5 agonist, betulinic acid, prior to AOM injection delayed neurological decline, increased cortical cyclic adenosine monophosphate concentrations, reduced microglia activation and proliferation, and reduced proinflammatory cytokine production. Betulinic acid treatment in vitro reduced the neuronal expression of chemokine ligand 2, a chemokine previously demonstrated to contribute to HE pathogenesis. Lastly, treatment of the microglia cell line EOC‐20 with conditioned media from betulinic acid‐treated primary neurons decreased phagocytic activity and cytokine production. Together, these data identify that activation of TGR5, which is up‐regulated during HE, alleviates neuroinflammation and improves outcomes of AOM‐treated mice through neuron and microglia paracrine signaling. <boxed-text content-type="graphic" id="jnc13243-blkfxd-0002" position="anchor" orientation="portrait"> </boxed-text> This study supports that betulinic acid infusion into the brain during hepatic encephalopathy reduces the release of the neuronal cytokine CCL2 and subsequently inhibits proinflammatory cytokine release from microglia. This improves neurological outcomes in a mouse model of hepatic encephalopathy and identifies a potential therapeutic target for management of this disease.